Approaches to suggest potential agreements: Perspectives of mediation with incomplete information - Sarabando, Paula (2015)
In bilateral Negotiation Analysis, the literature often co nsiders the case of complete information. In this context, since the negotiators know the value functions of both parties, it is not difficult to calculate the Pareto frontier and the Pareto efficient soluti ons for the negotiation. Thus rational negotiators can reach agreement on this frontier. However, these approaches are not applied in practice when the parties do not have complete information. The research question of our work is “It is possible to help negotiators achieving an efficient soluti on if they do not have complete information regarding the different parameters of the model?”. We propos e to obtain information regarding the preferences of negotiators during the negotiation process , in order to be able to propose alternatives close to the Pareto frontier. During this work we will presen t three approaches to help a mediator proposing a better solution than the compromise the negotia tors have reached or are close to reach.